The world book encyclopedia (Chicago, 2001)
An encyclopedia designed especially to meet the needs of elementary, junior high, and senior high school students. In all, this edition contains 85 new articles and revisions to about 2300 other entries. Of the latter, 185 were "extensively revised" or expanded, including the articles on "Government," "Celiac Disease," and "Terrorism"…
Keywords: Encyclopedias and dictionaries